Impact of Temporomandibular Joint Complaints on Tinnitus-Related Distress - Edvall, Niklas K.; Gunan, Edis; Genitsaridi, Eleni; Lazar, Andra; Mehraei, Golbarg; Billing, Mattias; Tullberg, Marie; Bulla, Jan; Whitton, Jonathon; Canlon, Barbara; Hall, Deborah A.; Cederroth, Christopher R. (Frontiers in Neuroscience, 2019)
There is increasing evidence of associations between the presence of temporomandibular joint (TMJ) disorders and tinnitus. It has been recently proposed that tinnitus patients with TMJ complaints could constitute a subtype, meaning a subgroup of tinnitus patients responsive to specific treatments. Tinnitus patients with TMJ complaints are often young women with somatosensory features of their tinnitus. Here, we investigate the socio-economic factors, phenotypic characteristics and psychological variables of tinnitus subjects from the Swedish Tinnitus Outreach Project, with (n=486) or without (n=1,996) TMJ complaints. The prevalence of TMJ complaints was greater in tinnitus subjects with severe tinnitus (36%) when compared to those with any tinnitus (19%), strongly indicating the contribution of TMJ problems to the severity of tinnitus. Comparing subgroups with or without TMJ complaints in the whole sample, differences were found regarding a large number of socioeconomic, phenotypic and psychological characteristics. Subjects with TMJ complaints were more often women, more often reported stress as the cause of tinnitus, were more severely affected by tinnitus, scored worse in measures of psychological well-being and life quality, and were more often affected by problems tolerating sounds, headache, vertigo/dizziness, and neck pain. In addition, they more often reported pulsating and tonal tinnitus, somatic modulation of tinnitus, and aggravation of tinnitus by loud sounds and stress. When focusing the analysis in subjects with tinnitus as a big problem using the Tinnitus Functional Index cut-off ≥ 48, or with severe tinnitus according to the Tinnitus Handicap Inventory cut-off ≥ 58, the impact of somatosensory modulations and stress on tinnitus were greater in subjects with TMJ complaints in comparison to those without. In light of these results, we hypothesize that stress could contribute to the co-occurrence of TMJ problems and tinnitus and also to the development of severe tinnitus. Our study supports the need of involving dental care and stress management in the holistic treatment of patients with severe tinnitus.